2022
DOI: 10.1371/journal.pone.0264216
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific effectiveness of a tuberculosis screening intervention in children

Abstract: Objective To apply a cascade-of-care framework to evaluate the effectiveness—by age of the child—of an intensified tuberculosis patient-finding intervention. Design From a prospective screening program at four hospitals in Pakistan (2014–2016) we constructed a care cascade comprising six steps: screened, positive screen, evaluated, diagnosed, started treatment, and successful outcome. We evaluated the cascade by each year of age from 0 to 14 and report the age-specific mean proportion and standard deviation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For both drug-susceptible and RR/MDR M.tb infection treatment, the first step is ruling out active TB disease. This is usually conducted through a symptom assessment, weight monitoring, physical examination, bacteriologic testing, and chest radiography [ 27 ]. Tests for M.tb infection perform poorly as they require a functioning immune system and are, thus, more likely to yield false-negative results in the populations most at risk of becoming sick with TB, such as in young children or persons living with HIV [ 28 ].…”
Section: Optimizing Rr/mdr-tb Prevention Through Systematic Post-expo...mentioning
confidence: 99%
“…For both drug-susceptible and RR/MDR M.tb infection treatment, the first step is ruling out active TB disease. This is usually conducted through a symptom assessment, weight monitoring, physical examination, bacteriologic testing, and chest radiography [ 27 ]. Tests for M.tb infection perform poorly as they require a functioning immune system and are, thus, more likely to yield false-negative results in the populations most at risk of becoming sick with TB, such as in young children or persons living with HIV [ 28 ].…”
Section: Optimizing Rr/mdr-tb Prevention Through Systematic Post-expo...mentioning
confidence: 99%
“…Four studies included in this systematic review indicated that the TST and IGRA tests were utilized as the first screening in paediatric patients with probable tuberculosis. Brooke et al 14 emphasized a history of symptoms suggestive of tuberculosis as initial screening, such with a TB patient in the previous two years and symptoms such as swollen glands, cough for more than two weeks, fever for more than two weeks, sweating, and unexplained weight loss. Four more studies compared the TST test and the IGRA test as screening tools and discovered that the TST test was more successful in terms of accuracy and cost effectiveness.…”
Section: Screening Of Paediatric Tb Patientsmentioning
confidence: 99%
“…The program depended mainly on clinical TB diagnosis and sputum samples. This emphasizes the relevance of TB history, physical examination, contact and exposure history, and chest X-ray findings in diagnosing children with TB, as well as the need for more accurate clinical prediction techniques 19. According to other research, aside from taking a past medical history, further procedures such as TST and IGRA tests are required for TB screening.…”
mentioning
confidence: 99%
“…Elsewhere, we describe details of the screening procedures used. [8][9][10] Children received a clinical evaluation, including chest radiograph, complete blood count and erythrocyte sedimentation rate, and-if they could produce sputum-additional testing such as Xpert MTB/RIF assay and acid fast bacilli smear. If indicated, abdominal ultrasound, computed tomography and/or fine-needle aspiration/biopsy were performed.…”
Section: Setting Intervention and Definitionsmentioning
confidence: 99%